Structural plastics selection manual (ASCE, 1985)
Prepared by the Task Committee on Properties of Selected Plastics Systems of the Structural Plastics Research Council of the Technical Council on Research of ASCE. Structural Plastics Manual presents information for the structural engineer regarding the selection of the proper material or combination of materials that will provide those properties (mechanical, physical, thermal, or whatever) upon which design assumptions and calculations are based. Essential differences between plastics and other structural materials are described along with the associated differences in material selection philosophies. Guidelines for materials selection procedures are given. Factors affecting properties during production and use are examined. A section on reliability and quality control is also included. Test procedures for physical and mechanical properties and environmental effects are described. This manual supplements the Structural Plastics Design Manual, MOP 63 (now out of print).
"Companion to the ASCE structural plastics design manual"--Title page verso.
Keywords: Plastics -- Handbooks, manuals, etc.; Structural design -- Handbooks, manuals, etc.; elektronické knihy; electronic books